Tipe Perbungaan Asteraceae di Air Terjun Irenggolo Kediri: - Sari, Devi Anita; Sulistiono, Sulistiono; Santoso, Agus Muji (Universitas Nusantara PGRI Kediri, 2022)
The Asteraceae family is a plant with attractive flower characteristics in terms of colour and size. Most of the flowers of this family are often infested by insects, especially the butterfly race. The tourist area of the Irenggolo waterfall was chosen as the research site because the area is still natural, with cold air temperatures allowing the abundance of the Asteraceae to thrive. This study was conducted to describe the type of inflorescence in each Asteraceae found. This type of research is descriptive qualitative with a survey method. Of the six species found, all of them are types of infinite and unbranched compound flowers; tube flowers have many similarities in the number of organs. The striking difference lies in the species Ageratum conyzoides L., which does not have ribbon flowers and has some pappus (petals) of 4. It is necessary to conduct further research regarding the causes of different types of ribbon flower layers in a population.